Crack Propagation Observation Using Digital Image Correlation (DIC) on Oil Palm Shell (OPS) Reinforced Concrete Beam - Handika, Nuraziz; Astutiningsih, Sotya; Sentosa, Bastian Okto Bangkit; Gasti, Muhammad Daffa (Jurnal Teknik Sipil dan Lingkungan, 2024)
In terms of disaster risk management, crack opening and behaviour of structural elements should be predicted to prevent severe risk after the failure. To do so, structure responses, and crack propagation phenomena of concrete structural elements should be understood. Opening, re-closing, or re-opening of cracks in concrete may occur under some circumstances. Capturing the behaviour along the test, sometimes, becomes a problem. Measurement tools should be detached to prevent damage as the sample reaches failure point. A set of contactless devices, called Digital Image Correlation (DIC), has been developed in the Laboratory of Structural and Material Universitas Indonesia. In this research, experimental on Oil Palm Shell (OPS) concrete beam with 19 MPa of fc’, was conducted under four-point loading in the laboratory. OPS is a solid by-product obtained from palm oil production. This experiment uses a 300 x 15 x 250 cm3 beam under a semi-cyclic loading protocol. Load vs deflection, strain, and cracking behaviour are obtained by using the DIC system as its equipment. The conventional measurement (dial gauge) results were compared to the DIC results. The measurement from both tools has similar values. Also, this DIC system can capture deflection and measure crack opening evolution along the test.